Military avionics systems - Moir, I. (Ian) (Aerospace series, 2006)
Military avionics is a complex and technically challenging field which requires a high level of competence from all those involved in the aircraft design and maintenance. This book introduces the military roles expected of aircraft types and describes the avionics systems required to fulfill these roles.